Intramuscular lipids of Mertolenga-PDO beef, Mertolenga-PDO veal and “Vitela Tradicional do Montado”-PGI veal - a. C.G. Monteiro; Fontes, M. a; Bessa, R. J. B.; Prates, J. a M.; Lemos, J. P. C. (Food Chemistry, 2012)
Three quality branded meats (n = 68), ‘‘Vitela Tradicional do Montado’’-PGI veal, Mertolenga-PDO veal and Mertolenga-PDO beef were analysed for cholesterol (HPLC-UV), a-tocopherol (HPLC-FD), fatty acid composition (GC-FID), including conjugated linoleic acid (CLA) isomeric proﬁle (Ag + -HPLC), and nutritional value of lipids. All the meats analysed had similar contents (P > 0.05) of cholesterol, a-tocopherol and intramuscular fat. In contrast, the percentage of 18:0 was lower for PGI veal, and that of 18:1 c9 was higher in PDO veal, whilst the percentage of 18:2 n6 was higher in PDO beef, relative to other two meats. The content of total CLA and the percentage of its t11,c13 isomer were higher, and the n6/ n3 ratio was lower, in PDO veal, relative to the other two meats. The data suggested that PGI veal has higher variability for most fatty acids than the other two types of meat. Finally, a discriminant analysis was conducted and the three meat types were well discriminated using the meat fatty acid proﬁle as variables.
The following values have no corresponding Zotero field: label: Beef;CLA isomers;Cholesterol;Fatty acids;Meat quality;a-Tocopherol
Keywords: a-tocopherol; Beef; Cholesterol; CLA isomers; fatty acids; meat quality

Fatty acid composition, conjugated linoleic acid isomers and cholesterol in beef from crossbred bullocks intensively produced and from Alentejana purebred bullocks reared according to Carnalentejana-PDO specifications. - Alfaia, C. M. M.; Ribeiro, V. S. S.; Lourenço, M. R. a; Quaresma, M. a G.; Martins, S. I. V.; Portugal, a P. V.; Fontes, C. M. G. a; Bessa, R. J. B.; Castro, M. L. F.; Prates, J. a M. (Meat science, 2006)
The purpose of this study was to characterise and compare the nutritional value of Portuguese Carnalentejana-PDO beef, obtained from Alentejana purebred bullocks reared in a semi-extensive system, with the meat from Alentejana×Charolais crossbred bullocks produced in a conventional intensive concentrate-based system. In addition, seasonal changes in Carnalentejana-PDO beef quality were assessed, by analysing meat samples from animals slaughtered in early autumn and late spring. The results showed that beef-PDO has different intramuscular fat characteristics in comparison with meat from crossbred bullocks fed intensively with concentrate. However, the finishing period of Alentejana purebred bullocks with concentrate seems to attenuate most of the typical grass-fed characteristics of meat fat. Nevertheless, from a human nutrition perspective, Carnalentejana-PDO beef seems to be healthier than that from intensively reared animals since it has a lower n-6/n-3 ratio, although always above the recommended guidelines for human diet, and higher proportions of c9,t11 conjugated linoleic acid (CLA) isomer and total CLA relative to saturated fatty acids plus total cholesterol (CLA/SFA+CHR). Furthermore, no seasonal variation in the nutritional quality of beef-PDO was apparent. Taken together, the data indicate that Carnalentejana-PDO beef is of greater nutritional value than intensively produced beef from crossbred bullocks throughout the year.
The following values have no corresponding Zotero field: accession-num: 22061726
Keywords: Beef; Cholesterol; CLA isomers; fatty acids; meat quality; Production systems

Fatty acid composition, conjugated linoleic acid isomers and cholesterol in beef from crossbred bullocks intensively produced and from Alentejana purebred bullocks reared according to Carnalentejana-PDO specifications. - Alfaia, C M M; Ribeiro, V S S; Lourenço, M R a; Quaresma, M a G; Martins, S I V; Portugal, a P V; Fontes, C M G a; Bessa, R J B; Castro, M L F; Prates, J a M (Meat science, 2006)
The purpose of this study was to characterise and compare the nutritional value of Portuguese Carnalentejana-PDO beef, obtained from Alentejana purebred bullocks reared in a semi-extensive system, with the meat from Alentejana×Charolais crossbred bullocks produced in a conventional intensive concentrate-based system. In addition, seasonal changes in Carnalentejana-PDO beef quality were assessed, by analysing meat samples from animals slaughtered in early autumn and late spring. The results showed that beef-PDO has different intramuscular fat characteristics in comparison with meat from crossbred bullocks fed intensively with concentrate. However, the finishing period of Alentejana purebred bullocks with concentrate seems to attenuate most of the typical grass-fed characteristics of meat fat. Nevertheless, from a human nutrition perspective, Carnalentejana-PDO beef seems to be healthier than that from intensively reared animals since it has a lower n-6/n-3 ratio, although always above the recommended guidelines for human diet, and higher proportions of c9,t11 conjugated linoleic acid (CLA) isomer and total CLA relative to saturated fatty acids plus total cholesterol (CLA/SFA+CHR). Furthermore, no seasonal variation in the nutritional quality of beef-PDO was apparent. Taken together, the data indicate that Carnalentejana-PDO beef is of greater nutritional value than intensively produced beef from crossbred bullocks throughout the year.
Keywords: Beef; Cholesterol; CLA isomers; fatty acids; meat quality; Production systems

Fatty acid composition, including isomeric profile of conjugated linoleic acid, and cholesterol in Mertolenga-PDO beef - Alfaia, Cristina M. M.; Quaresma, Mário A. G.; Castro, Matilde L. F.; Martins, Susana I. V.; Portugal, Ana P. V.; Fontes, Carlos M. G. A.; Bessa, Rui J. B.; Prates, José A. M. (Journal of the Science of Food and Agriculture, 2006)
This paper describes the fatty acid composition, including the isomeric distribution of conjugated linoleic acid (CLA), total lipids and cholesterol in longissimus dorsi (LD) and semitendinosus (ST) muscles of Mertolenga beef from young bulls reared according to Protected Designation of Origin (PDO) specifications. Mertolenga purebred young bulls (n = 30) were raised in a semi-extensive production system, including a finishing period on concentrate feeds for the last 5 or 3 months (October and June samplings, respectively). Mertolenga-PDO beef showed seasonal changes in the levels of some fatty acids (including the predominant 18:2n-6), sums of trans fatty acids and n-3 polyunsaturated fatty acids, some CLA isomers (t11,t13, t11,c13 and t10,c12), sums of geometric groups of CLA isomers and total cholesterol. In addition, significant differences were obtained between LD and ST muscles for most of the analysed parameters. From a nutritional perspective, beef-PDO from June seems to be more healthful than that from October as a consequence of its lower n-6/n-3 ratio. Moreover, the results suggest that the polyunsaturated fatty acid/saturated fatty acid ratio in the ST muscle is consistently above the recommended guideline for human diets, although the values were below that guideline for the LD muscle. Taken together, the data indicate that, although the finishing period of Mertolengo young bulls on concentrate attenuates most of the beneficial grass effects on meat fat throughout the year, beef-PDO from late spring is of greater nutritional value than that from early autumn. Copyright © 2006 Society of Chemical Industry
The following values have no corresponding Zotero field: publisher: John Wiley & Sons, Ltd.
Keywords: CLA isomers; fatty acids; meat quality; Mertolenga-PDO; total cholesterol; total lipids

Fatty acid composition, including isomeric profile of conjugated linoleic acid, and cholesterol in Mertolenga-PDO beef - Alfaia, Cristina M M; Quaresma, Mário A G; Castro, Matilde L F; Martins, Susana I V; Portugal, Ana P V; Fontes, Carlos M G A; Bessa, Rui J B; Prates, José A M (Journal of the Science of Food and Agriculture, 2006)
This paper describes the fatty acid composition, including the isomeric distribution of conjugated linoleic acid (CLA), total lipids and cholesterol in longissimus dorsi (LD) and semitendinosus (ST) muscles of Mertolenga beef from young bulls reared according to Protected Designation of Origin (PDO) specifications. Mertolenga purebred young bulls (n = 30) were raised in a semi-extensive production system, including a finishing period on concentrate feeds for the last 5 or 3 months (October and June samplings, respectively). Mertolenga-PDO beef showed seasonal changes in the levels of some fatty acids (including the predominant 18:2n-6), sums of trans fatty acids and n-3 polyunsaturated fatty acids, some CLA isomers (t11,t13, t11,c13 and t10,c12), sums of geometric groups of CLA isomers and total cholesterol. In addition, significant differences were obtained between LD and ST muscles for most of the analysed parameters. From a nutritional perspective, beef-PDO from June seems to be more healthful than that from October as a consequence of its lower n-6/n-3 ratio. Moreover, the results suggest that the polyunsaturated fatty acid/saturated fatty acid ratio in the ST muscle is consistently above the recommended guideline for human diets, although the values were below that guideline for the LD muscle. Taken together, the data indicate that, although the finishing period of Mertolengo young bulls on concentrate attenuates most of the beneficial grass effects on meat fat throughout the year, beef-PDO from late spring is of greater nutritional value than that from early autumn. Copyright © 2006 Society of Chemical Industry
Keywords: CLA isomers; fatty acids; meat quality; Mertolenga-PDO; total cholesterol; total lipids